KARAKTERISTIK FISIKOKIMIA DAN FUNGSIONAL TEKNIS TEPUNG KORO KRATOK (Phaseolus lunatus L.) TERMODIFIKASI YANG DIPRODUKSI SECARA FERMENTASI SPONTAN - Ahmad Nafi'; Nurud Diniyah; Febriani Tri Hastuti (AGROINTEK, 2015)
Lima bean (Phaseolus lunatus L.) has a high bioavailability and good of amino acidsbalanced. Lima bean was pontentially used as a food ingredient on food manufacturing. Inorder to enhance its properties, the bean flour wasmodified by spontaneous fermentation. Theaim of this research was to obtaine the appropriate fermentation pH and time on theproduction of modified lima bean flour. The fermentation pH were 4.5; 5 and 5.5 incombination with fermentation time of 16, 24 and 32 hour. The Modified lima bean flour wasthen determined its moisture, ash, fat and soluble protein content. viscosity, bulk density,lightening, oil holding capacity (OHC), water holding capacity (WHC), foaming activity andstability index, emulsifing activity and stability index. The research results showed that the besttreatment resulted by fermentation pH of 5.5 for 16 hours. The modified lima bean flour had8.10 ± 0.68 % water content, 5.52 ± 1.06 % ash content, 0.19 ± 2.18 % fat content, 33.74 ± 1.20% soluble protein content, 16 ± 0.00 mPas, hot viscosity, 17.33 ± 0.58 mPas cold viscosity, 0.88± 0.00 g/ml bulk density, 91.43 ± 0.38 brightness, 250.01 ± 43.76% oil holding capacity (OHC),189.49 ± 9.17 % water holding capacity (WHC), 28.22 ± 0.40 ml/g foaming activity, 26.52 ±1.31 % foaming stability, 333.63 ± 6.70 m2/g emulsion activity and 3.66 ± 0.01 hour emulsionstability. Based on those properties, the modified lima bean flour showeh high potency on manyfood application.